2011
DOI: 10.1590/s1415-43662011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Produção de aquênio do girassol irrigado com água salobra

Abstract: RESUMOObjetivou-se com este trabalho verificar os componentes de produção e a produção de aquênios do girassol (Helianthus annuus L., variedade Embrapa 122/V-2000), sob irrigação com diferentes níveis de salinidade de água em ambiente protegido. Os tratamentos foram compostos de seis níveis de salinidade da água de irrigação (CEa): N1 -0,5; N2 -1,0; N3 -2,0; N4 -3,0; N5 -4,0 e N6 -5,0 dS m -1 a 25 o C, em delineamento inteiramente casualizado com 5 repetições. Avaliaram-se: o diâmetro interno do capítulo, núme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 15 publications
1
6
1
19
Order By: Relevance
“…Under saline conditions, water availability was reduced due to the decrease in the osmotic potential of the soil solution, forcing the plant to invest more vital reserves, such as sugars and carbohydrates, to absorb water and nutrients for growth and production (MUNNS; TESTER, 2008). A similar situation was reported by Travassos et al (2011), who observed losses of 9.64% per unit increase in water salinity, using the same sunflower cultivar under irrigation with water of salinity ranging from 0.5 to 5.0 dS m -1 . In contrast to the factor irrigation water salinity, N levels linearly stimulated the production of achenes, with an increment of 4.46 achenes per unit increase in N levels ( Figure 1B), i.e.…”
Section: Resultssupporting
confidence: 86%
“…Under saline conditions, water availability was reduced due to the decrease in the osmotic potential of the soil solution, forcing the plant to invest more vital reserves, such as sugars and carbohydrates, to absorb water and nutrients for growth and production (MUNNS; TESTER, 2008). A similar situation was reported by Travassos et al (2011), who observed losses of 9.64% per unit increase in water salinity, using the same sunflower cultivar under irrigation with water of salinity ranging from 0.5 to 5.0 dS m -1 . In contrast to the factor irrigation water salinity, N levels linearly stimulated the production of achenes, with an increment of 4.46 achenes per unit increase in N levels ( Figure 1B), i.e.…”
Section: Resultssupporting
confidence: 86%
“…No final do ensaio, aos 120 DAS, estimou-se a condutividade elétrica do extrato de saturação do solo (CEes) em base de condutividade elétrica da água de drenagem (CEad), utilizando a relação (CEes = 0,5 x CEad) recomendada por AYERS & WESTCOT (1999) e confirmada em estudo anterior em condições semelhantes às deste experimento (TRAVASSOS et al, 2011).…”
Section: Methodsunclassified
“…Farmers in many parts of the world have attempted to use low quality water resources, such as saline and wastewater, however, the use of these water sources, particularly in the case of irrigated agriculture, depends on long-term strategies that ensure socioeconomic and environmental sustainability of the agricultural systems (MALASH et al, 2005;MURTAZA et al, 2006;TRAVASSOS et al, 2011;OSTER et al, 2012).…”
Section: Introductionmentioning
confidence: 99%